Estrategia de marcas propias de abarrotes comestibles en los supermercados de la ciudad de Barranquilla: caso Olímpica (2018)
The great advance of the retail sector in Colombia placed it, in 2016, in the second place among the Latin American countries in the Global Retail Development Index (GRDI, for its acronym in English) ranking prepared by the international consulting firm A.T. Kearney One criterion evaluated is the saturation of the market, a dimension that although it has had an important growth, it still evidences the need to increase retail space per inhabitant by almost double, to reach the density that would allow it to head the list (Pérez, 2016 ). Due to the dynamics and projection of the sector, the present research explored the key variables of the sector in Barranquilla, the key strategies for customer loyalty and categorized and described in a specific way, the strategy of own brands used by the Olympic group in the Barranquilla city, which have been key to its growth. The descriptive study, collected information from documentary sources and in the collection of primary information was observed consumer behavior and in-depth interviews with key personnel at the 12 points of sale, (9 Olympic Superstores and 3 Olympic Super Stores - SAO) located in the different socioeconomic strata in the city of Barranquilla. The technique of analysis and interpretation of statistical data uses the SPSS method. Among the most important findings, it was found that Olímpica has obtained a 20% participation in the total of its sales through its own brand strategy and a greater increase is expected with the implementation of combined strategies of differentiation, iteration, and exclusivity. In conclusion, marketing strategies are proposed that will allow the potentialization of own brands based on the knowledge acquired in the research process.